Vorkommen und Zug der Rauhhautfledermaus (Pipistrellus nathusii Keyserling und Blasius, 1839) in Baden-Württemberg - Bastian, Von H V (Zenodo, 1988)
(Uploaded by Plazi for the Bat Literature Project) The occurrence and migration of Nathusius' pipistrelle (Pipistrellus nathusii Keyserling & Blasius, 1839) in Baden-Württemberg During the whole year Nathusius' pipistrelle can be found in southwest Germany, but not one record of reproduction is known from Baden-Württemberg. Pipistrellus nathusii is much more frequent in autumn and late summer (about 85 % of all records) than in other seasons. Therefore it is supposed, that this species is normally migratory in southwest Germany and hibernates there only seldom, but more in southern countries (e.g. France). It could be shown that Nathusius' pipistrelle arrives 10 days earlier at the north eastern part of Baden-Württemberg than at Lake Konstanz and about four weeks earher than at the Regio Basiliensis. A possible migration route is discussed.